Catalytic cracking catalyst as well as preparation method and application thereof
By using a catalyst composed of phosphorus-containing ZSM-5 molecular sieve, binder and clay, the existing catalysts have been solved, and the problems of low conversion rate, low product yield and high coke generation in the catalytic cracking reaction of naphtha are solved, and an efficient catalytic cracking reaction is achieved.
Patent Information
- Application Number
- CN202311273825.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing catalytic cracking catalysts have problems such as low conversion rate, low product yield and high coke generation in naphtha catalytic cracking reaction.
The catalyst is prepared by a catalyst composed of phosphorus-containing ZSM-5 molecular sieve, binder and clay through specific preparation methods, including beating, spray drying and calcining. The mass content of the phosphorus-containing ZSM-5 molecular sieve of the catalyst is 60-80%, the mass content of clay is 5-20%, the mass content of the binder is 10-35%, the proportion of the strong acid acid to the total acid amount is 50-60%, and the ratio of the B acid acid amount to the L acid amount is 2-8.
The catalytic performance of the catalyst is improved, especially in naphtha catalytic cracking reaction, which has a high conversion rate and low carbon olefin yield, while reducing the formation of coke.
Smart Images

Figure BDA0004476297540000181 
Figure BDA0004476297540000182 
Figure BDA0004476297540000191
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic cracking catalyst preparation, and in particular to a catalytic cracking catalyst and a preparation method and application thereof. Background Art
[0002] At present, the main method for producing ethylene and propylene is steam thermal cracking. The most commonly used raw material is naphtha. However, steam thermal cracking of naphtha has the disadvantages of high reaction temperature, harsh process conditions, and release of a large amount of CO. 2 The catalytic cracking developed in recent years is a process for producing low-carbon olefins using petroleum hydrocarbons as raw materials, and there are many literature reports on the catalysts related to it.
[0003] CN114425417A discloses a naphtha catalytic cracking catalyst and its preparation method and application. The catalyst contains 50-85% by weight of a carrier and 15-50% by weight of a core-shell molecular sieve. However, the preparation method of the core-shell molecular sieve is relatively complicated.
[0004] CN1413244A discloses a method of using a modified mesoporous phosphate material as a catalyst in combination with a primary catalytic cracking material to catalytically crack sulfur-containing hydrocarbon raw materials to prepare a small molecule hydrocarbon mixture, but the catalyst has poor hydrothermal stability, and the conversion rate of the raw material and the product yield are both low.
[0005] CN109012742B discloses a catalyst for catalytic cracking of naphtha, which is composed of 65-80 wt% of LaZSM-5 molecular sieve and 20-35 wt% of Al 2 O 3 The catalyst has a composition of 0.3-1.7 wt % lanthanum. However, the catalyst is used in a multi-stage catalyst fixed bed adiabatic reactor for catalytic cracking of naphtha. The fixed bed adiabatic reactor contains 2-6 catalyst beds and needs to be coupled with methanol. The application is relatively complicated and is not conducive to industrial application.
[0006] CN105582999B discloses a catalyst for producing propylene by catalytic cracking of naphtha and a preparation method thereof, wherein the catalyst is based on the total weight of the catalyst, and the catalyst contains 50-95% by weight of a molecular sieve and 5-50% by weight of a matrix; the molecular sieve contains a first molecular sieve and a second molecular sieve, wherein the first molecular sieve is a molecular sieve having a two-dimensional elliptical channel structure of a ten-membered ring, and the second molecular sieve is a molecular sieve having a twelve-membered ring channel structure. The diene yield is high, but multiple molecular sieves are required as active centers, and the cost price is relatively high. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the prior art and provide a catalytic cracking catalyst and its preparation method and application. The catalyst of the present invention is applied to catalytic cracking reaction, especially to naphtha catalytic cracking reaction, and has a high conversion rate and low carbon olefin yield.
[0008] In order to achieve the above object, the present invention provides a catalytic cracking catalyst, which comprises a phosphorus-containing ZSM-5 molecular sieve, a binder and clay; based on the total mass of the catalyst, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-80%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%;
[0009] The proportion of the strong acid content of the catalyst to the total acid content is 50-60%;
[0010] The ratio of the amount of B acid to the amount of L acid in the catalyst is 2-8.
[0011] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:
[0012] (1) slurrying the phosphorus-containing ZSM-5 molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry;
[0013] (2) beating the first slurry with at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.2 Pa·s;
[0014] (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s;
[0015] (4) spray drying the third slurry and then calcining it;
[0016] Wherein, the average grain size of the phosphorus-containing ZSM-5 molecular sieve is 100-500nm.
[0017] The third aspect of the present invention provides a use of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in a catalytic cracking reaction.
[0018] Through the above technical solution, the beneficial effects of the present invention include:
[0019] The catalyst of the present invention contains phosphorus-containing ZSM-5 molecular sieve active components, and has high molecular sieve content and suitable acid properties, so that the catalyst of the present invention has excellent catalytic performance. The catalyst of the present invention is applied to catalytic cracking reaction, especially to naphtha catalytic cracking reaction, and has high conversion rate and low carbon olefin yield, and low coke yield. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] The dry basis of the present invention refers to that obtained by calcining at 550° C. for 2 hours.
[0022] In one aspect, the present invention provides a catalytic cracking catalyst, which comprises a phosphorus-containing ZSM-5 molecular sieve, a binder and clay; based on the total mass of the catalyst, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-80%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%;
[0023] The proportion of the strong acid content of the catalyst to the total acid content is 50-60%;
[0024] The ratio of the amount of B acid to the amount of L acid in the catalyst is 2-8.
[0025] The ratio of the B acid amount to the L acid amount of the prior art catalytic cracking catalyst is large, generally above 10, and although the conversion rate is high, it has the defect of being difficult to accurately control the product distribution. The present invention controls the ratio of the B acid amount to the L acid amount of the catalyst at a lower level, which is conducive to suppressing the generation of coke while ensuring the diene selectivity in the product distribution.
[0026] In order to further improve the catalytic performance of the catalyst, preferably, based on the total mass of the catalyst, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-70%, the mass content of the clay is 5-20%, and the mass content of the binder is 16-35%.
[0027] The total content of each component of the catalyst of the present invention is 100%.
[0028] The content of each component of the catalyst of the present invention is obtained by calculating the feed.
[0029] According to the present invention, preferably, the proportion of the strong acid content of the catalyst to the total acid content is 55-60%. By adopting this preferred embodiment, the raw material conversion rate can be improved.
[0030] The ratio of the strong acid content to the total acid content of the present invention is NH 3 -TPD method determination.
[0031] In the present invention, unless otherwise specified, the strong acid refers to an acid having an NH 3 The desorption temperature is greater than 300℃ corresponding to the acid center.
[0032] According to the present invention, preferably, the ratio of the B acid content to the L acid content of the catalyst is 3 to 8. By adopting this preferred embodiment, the generation of coke during the reaction can be reduced.
[0033] In the present invention, the ratio of the acid amount of B acid to the acid amount of L acid is determined by pyridine adsorption infrared acid method.
[0034] According to the present invention, preferably, based on the total mass of the phosphorus-containing ZSM-5 molecular sieve, P 2 O 5 The mass content of phosphorus is 1-12%, preferably 2-9%. By adopting this preferred embodiment, the stability of ZSM-5 molecular sieve in a high hydrothermal environment can be ensured.
[0035] The phosphorus content in the phosphorus-containing ZSM-5 molecular sieve of the present invention is measured by using an X-ray fluorescence spectrometry analysis method.
[0036] The present invention has no particular limitation on the source of the phosphorus-containing ZSM-5 molecular sieve, which can be prepared by conventional methods in the art or purchased commercially.
[0037] The present invention has a wide range of clay types, which can be selected from conventional choices in the art. Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.
[0038] According to the present invention, preferably, the adhesive includes a first adhesive, a second adhesive and a third adhesive.
[0039] According to the present invention, preferably, the first binder is obtained by calcining at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina.
[0040] The present invention has no particular limitation on the source of the first binder, which can be obtained from commercial sources or prepared by conventional methods.
[0041] According to the present invention, preferably, the second binder is obtained by calcining aluminum sol.
[0042] According to the present invention, preferably, the aluminum sol has an aluminum-chlorine ratio of no more than 1.4, preferably 1.2-1.3. This preferred embodiment can minimize the degree of damage to the molecular sieve framework while ensuring the bonding performance of the binder, which is beneficial to improving the reaction activity of the catalyst.
[0043] The aluminum-chlorine ratio of the aluminum sol described in the present invention is measured by X-ray fluorescence spectrometry.
[0044] The present invention has no particular limitation on the source of the aluminum sol, which can be obtained from commercial sources or prepared in-house according to conventional methods.
[0045] According to the present invention, preferably, the third binder is obtained by calcining phosphate-aluminum-magnesium glue.
[0046] The present invention has no particular limitation on the calcination conditions. For example, the calcination conditions may be the calcination conditions in the following preparation method.
[0047] According to the present invention, preferably, the mass ratio of the second binder to the first binder is 1-4, preferably 1.7-4.
[0048] According to the present invention, preferably, the mass ratio of the second binder to the third binder is 0.1-0.9, preferably 0.2-0.7.
[0049] According to the present invention, preferably, Al in the phosphate aluminum magnesium glue 2 O 3 With P 2 O 5 The mass ratio of MgO is 0.25-0.35, and the mass ratio of Al 2 O 3 With P 2 O 5 By adopting this preferred embodiment, the bonding performance of the binder can be guaranteed, and the acid sites provided by the binder can be precisely adjusted, thereby obtaining a lower coke selectivity.
[0050] The Al in the phosphate aluminum magnesium glue of the present invention 2 O 3 With P 2 O 5 The mass ratio was measured by X-ray fluorescence spectrometry.
[0051] The mass of MgO in the phosphate-aluminum-magnesium glue of the present invention is obtained by calculating the feed.
[0052] The present invention has no particular limitation on the preparation method of the above-mentioned phosphate-aluminum-magnesium gel, as long as the phosphate-aluminum-magnesium gel of the above-mentioned composition can be prepared. In order to further improve the catalytic performance of the catalyst, the present invention also provides a preparation method of the above-mentioned phosphate-aluminum-magnesium gel.
[0053] According to the present invention, preferably, the preparation method of the phosphate aluminum magnesium glue comprises:
[0054] (a) mixing an acid-soluble aluminum precursor with water and slurrying, and then adding a phosphoric acid solution at 45-55° C. to carry out a first reaction to obtain the phosphoaluminum gel;
[0055] (b) subjecting the phosphate aluminum gel obtained in step (a) to a second reaction with magnesium oxide to obtain the phosphate aluminum magnesium gel.
[0056] In the preparation method of the phosphate-aluminum-magnesium glue of the present invention, by controlling the temperature of adding phosphoric acid, preferably controlling the two-step reaction conditions, the composition of the prepared phosphate-aluminum-magnesium glue meets the above requirements, which is beneficial to the stability of the phosphate-aluminum-magnesium glue.
[0057] According to the present invention, preferably, the phosphoaluminum gel obtained in step (a) has a network structure.
[0058] The structure of the phosphoaluminum gel of the present invention is measured by a transmission electron microscope.
[0059] In the prior art, phosphate aluminum gel generally has a dispersed spherical nanoparticle structure, which has the defects of poor bonding performance and unstable structure. However, the inventors found in the research process that phosphate aluminum gel with a mesh structure has both excellent bonding performance and a stable skeleton structure, so that the prepared phosphate aluminum magnesium gel has excellent bonding performance and is conducive to improving the mechanical strength of the catalyst.
[0060] According to the present invention, preferably, the pH of the phosphate aluminum gel obtained in step (a) is 1-3, preferably 2-3. By adopting this preferred embodiment, the structure and stability of the phosphate aluminum gel binder can be ensured, while ensuring the stability of the molecular sieve structure, which is further conducive to improving the reaction activity and mechanical strength of the catalyst. The obtained phosphate aluminum magnesium gel can further regulate the overall acidity of the catalyst while ensuring the above advantages, thereby obtaining a lower coke selectivity.
[0061] According to the present invention, preferably, the conditions of the first reaction include: temperature of 75-85° C., and time of 1-2 h.
[0062] The present invention has no particular limitation on the amount of water used in step (a), so long as the pH of the phosphate aluminum gel is within the above range.
[0063] The present invention has no particular limitation on the acid-soluble aluminum precursor and phosphoric acid solution, so that in the obtained phosphate aluminum magnesium gel, Al 2 O 3 With P 2 O 5 The mass ratio is 0.25-0.35.
[0064] The present invention has a wide range of choices for the acid-soluble aluminum precursor, which can be a conventional choice in the art. Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide, preferably pseudo-boehmite.
[0065] According to the present invention, preferably, the conditions of the second reaction include: temperature of 15-35° C., and time of 8-12 h.
[0066] According to the present invention, preferably, the mass dosage of magnesium oxide is Al 2 O 3 With P 2 O 5 1-5% of the total mass.
[0067] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:
[0068] (1) slurrying the phosphorus-containing ZSM-5 molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry;
[0069] (2) beating the first slurry with at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.2 Pa·s;
[0070] (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s;
[0071] (4) spray drying the third slurry and then calcining it;
[0072] Wherein, the average grain size of the phosphorus-containing ZSM-5 molecular sieve is 100-500nm.
[0073] In the prior art, the molecular sieve content of the spray-formed catalyst is relatively low, generally not higher than 40wt%, which is mainly due to the need to ensure that the mechanical strength of the catalyst meets the requirements of the catalytic cracking reaction. When the molecular sieve content is too high, spray forming is more difficult, and the catalyst wear index is too high (higher than 10% / h), resulting in poor catalyst stability. The method provided by the present invention adopts a phosphorus-containing ZSM-5 molecular sieve with a specific average crystal size and other substances, and the catalytic cracking catalyst obtained by specific steps overcomes the above-mentioned defects, so that the mechanical strength of the prepared catalytic cracking catalyst meets the requirements of the catalytic cracking reaction, and it has a high molecular sieve content and suitable acid properties. It is applied to catalytic cracking reactions, especially to naphtha catalytic cracking reactions, with higher reactant conversion and ethylene propylene yield and lower coke yield.
[0074] In the present invention, the viscosity of the second slurry is not more than 0.2Pa·s, preferably 0.01-0.2Pa·s, for example, 0.01Pa·s, 0.02Pa·s, 0.03Pa·s, 0.04Pa·s, 0.05Pa·s, 0.06Pa·s, 0.07Pa·s, 0.08Pa·s, 0.09Pa·s, 0.1Pa·s, 0.11Pa·s, 0.12Pa·s, 0.13Pa·s, 0.14Pa·s, 0.15Pa·s, 0.16Pa·s, 0.17Pa·s, 0.18Pa·s, 0.19Pa·s, 0.2Pa·s, and any value in the range formed by any two of these values. This preferred embodiment is conducive to obtaining a uniform catalyst (i.e., each component is evenly distributed).
[0075] In the present invention, the viscosity of the third slurry is not less than 1Pa·s, preferably 1-3Pa·s, for example, 1Pa·s, 1.1Pa·s, 1.2Pa·s, 1.3Pa·s, 1.4Pa·s, 1.5Pa·s, 1.6Pa·s, 1.7Pa·s, 1.8Pa·s, 1.9Pa·s, 2Pa·s, 2.1Pa·s, 2.2Pa·s, 2.3Pa·s, 2.4Pa·s, 2.5Pa·s, 2.6Pa·s, 2.7Pa·s, 2.8Pa·s, 2.9Pa·s, 3Pa·s, and any value in the range formed by any two of these values. This preferred embodiment is conducive to improving the mechanical strength of the catalyst.
[0076] The viscosity of the present invention is measured by a viscometer.
[0077] The present invention has no particular limitation on the specific conditions of pulping (mentioned above and below) in the preparation method, and it can be carried out by conventional methods in the art, which is not limited here.
[0078] According to the present invention, preferably, the amounts of the clay, the phosphorus-containing ZSM-5 molecular sieve and the binder precursor are such that in the prepared catalyst, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-80%, and the mass content of the binder is 10-35%, and the binder is the sum of the first binder, the second binder and the third binder.
[0079] Further preferably, the amounts of the clay, phosphorus-containing ZSM-5 molecular sieve and binder precursor are such that in the prepared catalyst, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-70%, and the mass content of the binder is 16-35%, and the binder is the sum of the first binder, the second binder and the third binder.
[0080] According to the present invention, preferably, the dry weight ratio of the second binder precursor to the first binder precursor is 1-4, preferably 1.7-4.
[0081] According to the present invention, preferably, the dry basis mass ratio of the second binder precursor to the third binder precursor is 0.1-0.9, preferably 0.2-0.7.
[0082] According to the present invention, preferably, the average crystal size of the phosphorus-containing ZSM-5 molecular sieve is 200-300 nm. This preferred embodiment is beneficial to increase the contact probability between the reactants and the catalytic active sites, thereby improving the reaction activity of the catalyst.
[0083] In the present invention, when the crystal grains are spherical, the crystal grain size refers to the crystal grain diameter; when the crystal grains are quasi-spherical, the crystal grain size refers to the diameter of the largest circumscribed circle thereof.
[0084] The average grain size of the present invention is measured by transmission electron microscopy, specifically, 10 molecular sieve grains are randomly selected, their grain sizes are measured, and then the average value is obtained.
[0085] According to the present invention, preferably, the SiO 2 / Al 2 O 3 The molar ratio is 20-200, preferably 25-100, for example, it can be 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, and any value in the range formed by any two of these values. The use of this preferred embodiment is conducive to improving the catalytic activity of the catalyst. When the SiO 2 / Al 2 O 3 When the molar ratio is higher than this range, the number of active sites of the catalyst is reduced and the catalytic activity of the catalyst is significantly reduced.
[0086] According to the present invention, preferably, based on the total mass of the phosphorus-containing ZSM-5 molecular sieve, P 2 O 5The phosphorus content is 1-12% by mass, preferably 2-9% by mass.
[0087] The present invention has no particular limitation on the source of the phosphorus-containing ZSM-5 molecular sieve, which can be prepared by conventional methods in the art or purchased commercially.
[0088] The present invention has a wide range of clay types, which can be selected from conventional choices in the art. Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.
[0089] According to the present invention, preferably, the first binder precursor is selected from at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina.
[0090] According to the present invention, preferably, the second binder precursor is aluminum sol.
[0091] According to the present invention, preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3.
[0092] The present invention has no particular limitation on the source of the aluminum sol, which can be obtained from commercial sources or prepared in-house according to conventional methods.
[0093] According to the present invention, preferably, the third binder precursor is phosphate aluminum magnesium glue.
[0094] According to the present invention, preferably, Al in the phosphate aluminum magnesium glue 2 O 3 With P 2 O 5 The mass ratio of MgO is 0.25-0.35, and the mass ratio of Al 2 O 3 With P 2 O 5 1-5% of the total mass.
[0095] According to the present invention, preferably, the preparation method of the phosphate aluminum magnesium glue comprises:
[0096] (a) mixing an acid-soluble aluminum precursor with water and slurrying, and then adding a phosphoric acid solution at 45-55° C. to carry out a first reaction to obtain the phosphoaluminum gel;
[0097] (b) subjecting the phosphate aluminum gel obtained in step (a) to a second reaction with magnesium oxide to obtain the phosphate aluminum magnesium gel.
[0098] According to the present invention, preferably, the phosphoaluminum gel obtained in step (a) has a network structure.
[0099] According to the present invention, preferably, the pH of the phosphate aluminum gel obtained in step (a) is 1-3, preferably 2-3.
[0100] According to the present invention, preferably, the conditions of the first reaction include: temperature of 75-85° C., and time of 1-2 h.
[0101] The present invention has no particular limitation on the acid-soluble aluminum precursor and phosphoric acid solution, so that in the obtained phosphate aluminum magnesium gel, Al 2 O 3 With P 2 O 5 The mass ratio is 0.25-0.35.
[0102] The present invention has no particular limitation on the amount of water used in step (a), so long as the pH of the phosphate aluminum gel is within the above range.
[0103] The present invention has a wide range of choices for the acid-soluble aluminum precursor, which can be a conventional choice in the art. Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide, preferably pseudo-boehmite.
[0104] According to the present invention, preferably, the conditions of the second reaction include: temperature of 15-35° C., and time of 8-12 h.
[0105] According to the present invention, preferably, the mass dosage of magnesium oxide is Al 2 O 3 With P 2 O 5 1-5% of the total mass.
[0106] The present invention has no particular limitation on the order of adding the phosphorus-containing ZSM-5 molecular sieve, the second suspension containing clay and the first binder precursor in step (1), and they can be added separately or together. The embodiment of the present invention adopts the method of adding them together as an example.
[0107] Preferably, the phosphorus-containing ZSM-5 molecular sieve is provided in the form of a first suspension.
[0108] The present invention has a wide range of choices for the type of the first liquid medium in the first suspension, which can be a conventional choice in the art. Preferably, the first liquid medium is water and / or an organic solvent, preferably water.
[0109] The present invention has no particular limitation on the amount of the first liquid medium in the first suspension, as long as the solid content in the first suspension is within 30-40 wt %.
[0110] According to the present invention, preferably, the second suspension is obtained by slurrying clay, the second liquid medium and optionally the remaining part of the second binder precursor. With this preferred embodiment, the clay has good fluidity while ensuring that the solid content of the second suspension is maintained at a high level.
[0111] According to the present invention, preferably, the dry basis mass of the remaining second binder precursor is 5-15% of the dry basis mass of the clay.
[0112] The present invention has a wide range of choices for the type of the second liquid medium in the second suspension, and can be a conventional choice in the art.
[0113] According to a preferred embodiment of the present invention, the second liquid medium is of the same type as the first liquid medium.
[0114] The present invention has no particular limitation on the amount of the second liquid medium in the second suspension, as long as the solid content in the second suspension is within the range of 28-40 wt %.
[0115] Preferably, the first binder precursor is provided in the form of a third suspension.
[0116] Preferably, the preparation method of the third suspension comprises: firstly slurrying the first binder precursor and the third liquid medium, and then mixing them with an acid.
[0117] Preferably, the acid is an inorganic acid, preferably hydrochloric acid and / or nitric acid. The above substances are conventionally selected in the art and can be obtained commercially.
[0118] Preferably, the weight ratio of the acid to the first binder precursor on a dry basis is 0.1-1:1.
[0119] The present invention has a wide range of choices for the type of the third liquid medium in the third suspension, which can be a conventional choice in the art.
[0120] According to a preferred embodiment of the present invention, the third liquid medium is of the same type as the first liquid medium.
[0121] The present invention has no particular limitation on the amount of the third liquid medium in the third suspension, as long as the solid content in the third suspension is within the range of 10-25 wt %.
[0122] The present invention has no particular limitation on the specific conditions of the spray drying in step (4), which can be carried out according to conventional methods in the art, and the present invention does not impose any limitation thereon.
[0123] The present invention has no particular limitation on the conditions for the calcination in step (4), and the calcination may be carried out according to conventional methods in the art. Preferably, the calcination conditions in step (4) include: a temperature of 400-800° C. and a time of 1-12 h. The calcination is generally carried out in an air atmosphere, which may include a flowing atmosphere or a static atmosphere.
[0124] In the present invention, the "first", "second" and "third" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.
[0125] The third aspect of the present invention provides an application of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in a catalytic cracking reaction, preferably in a catalytic cracking reaction of naphtha.
[0126] Preferably, the application process comprises: contacting the crude oil with a catalytic cracking catalyst for reaction.
[0127] The present invention has no particular limitation on the conditions of the catalytic cracking reaction, and the reaction can be carried out according to conventional methods in the art. Preferably, the conditions of the contact reaction include: a temperature of 580-650°C.
[0128] Preferably, the mass ratio of catalyst to feedstock oil is 3-10.
[0129] The present invention has a wide range of selection for the type of the raw oil. Preferably, the raw oil is naphtha.
[0130] In order to better illustrate the stability of the catalyst of the present invention in the application of catalytic cracking reaction, it was hydrothermally aged before use.
[0131] The hydrothermal aging temperature of the catalytic cracking catalyst in the prior art is generally not more than 800°C, and the time is also relatively short, generally not more than 17 hours. The aging conditions of the hydrothermal aging described in the present invention are more stringent, and are used to better reflect the actual application degree of the industry. Preferably, the hydrothermal aging conditions include: a temperature of 820-850°C and a time of 20-72 hours.
[0132] Preferably, the hydrothermal aging is carried out under the condition of 100% water vapor.
[0133] The present invention will be described in detail below through examples.
[0134] In the following examples, the aluminum sol is a commercial product of Sinopec Catalyst Company Qilu Branch, with a solid content of 21.5% by weight;
[0135] Pseudo-boehmite is a commercial product from Shandong Aluminum Plant, with a solid content of 66.9 wt %;
[0136] Kaolin was a commercial product from Suzhou Kaolin Company, with a dry basis mass of 84.6% by weight.
[0137] Preparation Examples 1-3 are used to illustrate the preparation of the phosphate-aluminum-magnesium gel of the present invention.
[0138] Preparation Example 1
[0139] (a) 1.1 kg of pseudo-boehmite and 2.9 kg of deionized water were weighed and slurried evenly, then heated to 50° C., 4 kg of phosphoric acid (concentration 85 wt%) was added, and heated to 80° C. for 90 min to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure and a pH of 2.
[0140] (b) Weigh 0.16 kg of solid magnesium oxide (product of Sinopec Catalyst Company Qilu Branch, solid content 98.5%) and add it to the above-mentioned phosphate aluminum gel, react at room temperature for 12 hours to prepare phosphate aluminum magnesium gel. 2 O 3 With P 2 O 5 The mass ratio of MgO is 0.3, and the mass ratio of Al 2 O 3 With P 2 O 5 5% of the total mass.
[0141] Preparation Example 2
[0142] (a) 1.18 kg of pseudo-boehmite and 2.82 kg of deionized water were weighed and slurried evenly, then heated to 45° C., 4 kg of phosphoric acid (concentration 85 wt%) was added, and heated to 80° C. for 60 min to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure and a pH of 2.2.
[0143] (b) Weigh 0.1 kg of solid magnesium oxide (product of Sinopec Catalyst Company Qilu Branch, solid content 98.5%) and add it to the above-mentioned phosphate aluminum gel, react at room temperature for 8 hours to prepare phosphate aluminum magnesium gel.
[0144] The Al in the phosphate aluminum magnesium glue 2 O 3 With P 2 O 5 The mass ratio of MgO is 0.32, and the mass ratio of Al 2 O 3 With P 2 O 5 3% of the total mass.
[0145] Preparation Example 3
[0146] (a) Weigh 0.83 kg of pseudo-boehmite and 2.18 kg of deionized water, slurry them evenly, then heat them to 55° C., add 3 kg of phosphoric acid (concentration 85 wt%), heat to 75° C., and react for 60 min to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure and a pH of 2.5.
[0147] (b) Weigh 0.02 kg of solid magnesium oxide (product of Sinopec Catalyst Company Qilu Branch, solid content 98.5%) and add it to the above-mentioned phosphate aluminum gel, react at room temperature for 8 hours to prepare phosphate aluminum magnesium gel.
[0148] The Al in the phosphate aluminum magnesium glue 2 O 3 With P 2 O 5 The mass ratio of MgO is 0.3, and the mass ratio of Al 2 O 3 With P 2 O 5 1% of the total mass.
[0149] Example 1
[0150] The preparation method of phosphorus-containing ZSM-5 molecular sieve comprises: dissolving diammonium hydrogen phosphate with 6.65 kg of deionized water to obtain diammonium hydrogen phosphate aqueous solution, impregnating ZSM-5 molecular sieve with diammonium hydrogen phosphate aqueous solution, drying at 120° C., and calcining at 550° C. for 2 hours to obtain phosphorus-containing ZSM-5 molecular sieve with a dry basis mass of 97 weight %.
[0151] Weigh 6.65kg of phosphorus-containing ZSM-5 molecular sieve and slurry with deionized water to prepare a phosphorus-containing ZSM-5 molecular sieve suspension with a solid content of 33wt%. Weigh 0.85kg of kaolin, 0.33kg of aluminum sol and deionized water respectively and slurry them to prepare a kaolin suspension with a solid content of 38wt%. Weigh 0.32kg of pseudo-boehmite and slurry them with deionized water to prepare a pseudo-boehmite suspension with a solid content of 17wt%. Then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.13) to prepare a pseudo-boehmite suspension with a solid content of 17wt%. Slurry the above kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15min to obtain a first slurry. Add 1.67kg of aluminum sol to the first slurry and slurry for 5min to obtain a second slurry. Add 5.2kg of phosphorus aluminum magnesium glue obtained in Preparation Example 1 to the second slurry and slurry for 5min to obtain a third slurry. The third slurry was spray dried and then calcined at 550° C. for 2 hours to obtain a catalyst, which was recorded as A. Some conditions in the preparation process of catalyst A are shown in Table 1. The composition and characteristic parameters of catalyst A are shown in Table 2.
[0152] Example 2
[0153] The preparation method of phosphorus-containing ZSM-5 molecular sieve comprises: dissolving diammonium hydrogen phosphate with 12.26 kg of deionized water to obtain diammonium hydrogen phosphate aqueous solution, impregnating ZSM-5 molecular sieve with diammonium hydrogen phosphate aqueous solution, drying at 120° C., and calcining at 550° C. for 2 hours to obtain phosphorus-containing ZSM-5 molecular sieve with a dry basis mass of 97 weight %.
[0154] Weigh 12.26kg of phosphorus-containing ZSM-5 molecular sieve and slurry with deionized water to prepare a phosphorus-containing ZSM-5 molecular sieve suspension with a solid content of 36wt%. Weigh 2.54kg of kaolin, 1.4kg of aluminum sol and deionized water respectively and slurry them to prepare a kaolin suspension with a solid content of 38wt%. Weigh 0.96kg of pseudo-boehmite and slurry them with deionized water, then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.12) to prepare a pseudo-boehmite suspension with a solid content of 21wt%. Slurry the above-mentioned kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 4.18kg of aluminum sol to the first slurry and slurry for 5 minutes to obtain a second slurry. Add 9.67kg of phosphorus aluminum magnesium glue obtained in Preparation Example 2 to the second slurry and slurry for 5 minutes to obtain a third slurry. The third slurry was spray dried and then calcined at 550° C. for 2 hours to obtain a catalyst, which was denoted as B. Some conditions in the preparation process of catalyst B are shown in Table 1. The composition and characteristic parameters of catalyst B are shown in Table 2.
[0155] Example 3
[0156] The preparation method of phosphorus-containing ZSM-5 molecular sieve comprises: dissolving diammonium hydrogen phosphate with 10.74 kg of deionized water to obtain diammonium hydrogen phosphate aqueous solution, impregnating ZSM-5 molecular sieve with diammonium hydrogen phosphate aqueous solution, drying at 120° C., and calcining at 550° C. for 2 hours to obtain phosphorus-containing ZSM-5 molecular sieve with a dry basis mass of 97 weight %.
[0157] Weigh 10.74kg of phosphorus-containing ZSM-5 molecular sieve and slurry with deionized water to prepare a phosphorus-containing ZSM-5 molecular sieve suspension with a solid content of 31wt%. Weigh 2.12kg of kaolin, 0.5kg of aluminum sol and deionized water to slurry to prepare a kaolin suspension with a solid content of 30wt%. Weigh 0.45kg of pseudo-boehmite and slurry with deionized water to prepare a pseudo-boehmite suspension with a solid content of 20wt%. Then add concentrated hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.1) to prepare a pseudo-boehmite suspension with a solid content of 20wt%. Slurry the above kaolin suspension, pseudo-boehmite suspension and phosphorus-containing ZSM-5 molecular sieve suspension for 15min to obtain a first slurry. Add 3.14kg of aluminum sol to the first slurry and slurry for 5min to obtain a second slurry. Add 3.9kg of phosphorus aluminum magnesium glue obtained in Preparation Example 3 to the second slurry and slurry for 5min to obtain a third slurry. The third slurry was spray dried and then calcined at 550° C. for 2 hours to obtain a catalyst, which was recorded as C. Some conditions in the preparation process of catalyst C are shown in Table 1. The composition and characteristic parameters of catalyst C are shown in Table 2.
[0158] Example 4
[0159] The method of Example 1 was followed, except that the average crystal size of the phosphorus-containing ZSM-5 molecular sieve was 450 nm, to obtain a catalyst, which was recorded as D. Some conditions in the preparation process of catalyst D are shown in Table 1. The composition and characteristic parameters of catalyst D are shown in Table 2.
[0160] Comparative Example 1
[0161] The method of Example 1 was followed, except that the phosphate aluminum magnesium gel was not added to obtain a catalyst, which was recorded as E. Some conditions in the preparation process of catalyst E are shown in Table 1. The composition and characteristic parameters of catalyst E are shown in Table 2.
[0162] Comparative Example 2
[0163] The preparation method of phosphorus-containing ZSM-5 molecular sieve comprises: dissolving diammonium hydrogen phosphate with 4.09 kg of deionized water to obtain diammonium hydrogen phosphate aqueous solution, impregnating ZSM-5 molecular sieve with diammonium hydrogen phosphate aqueous solution, drying at 120° C., and calcining at 550° C. for 2 hours to obtain phosphorus-containing ZSM-5 molecular sieve with a dry basis mass of 97 weight %.
[0164] Weigh 4.09 kg of phosphorus-containing ZSM-5 molecular sieve and deionized water respectively and slurry them evenly to prepare a phosphorus-containing ZSM-5 molecular sieve suspension with a solid content of 30 wt%. Weigh 2.96 kg of kaolin and deionized water respectively and slurry them evenly to prepare a kaolin suspension with a solid content of 32 wt%. Weigh 1.49 kg of pseudo-boehmite and deionized water and slurry them evenly, then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.12) to prepare a pseudo-boehmite suspension with a solid content of 18 wt%. Slurry the above kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 5.5 kg of phosphorus aluminum magnesium glue obtained in the above Preparation Example 1 to the first slurry and slurry for 5 minutes to obtain a second slurry. The above second slurry is spray dried and then calcined at 550°C for 2 hours to obtain catalyst F. Some conditions in the preparation process of catalyst F are shown in Table 1. The composition and characteristic parameters of catalyst F are shown in Table 2.
[0165] Comparative Example 3
[0166] The method of Example 1 was followed, except that the phosphate aluminum magnesium gel obtained in Preparation Example 1 was not added to the third slurry, but the phosphate aluminum gel obtained in Preparation Example 1 was added, so that the mass ratio of the second binder to the third binder was still 0.2, to obtain a catalyst, which was recorded as G. Some conditions in the preparation process of catalyst G are shown in Table 1. The composition and characteristic parameters of catalyst G are shown in Table 2.
[0167] Comparative Example 4
[0168] The method of Example 1 was followed, except that 5.07 kg of phosphoaluminum glue obtained in Preparation Example 1 was added to the second slurry and slurried for 5 minutes to obtain a third slurry. 0.1 kg of magnesium oxide (a product of Sinopec Catalyst Company Qilu Branch, solid content 98.5%) was added to the third slurry, and then spray-dried and calcined at 550° C. for 2 hours to obtain a catalyst, denoted as H. In catalyst H, the molecular sieve content was 65 wt%, the binder content was 27 wt%, the clay content was 7 wt%, and the MgO content was 1 wt%.
[0169] Some conditions in the preparation process of catalyst H are shown in Table 1. The composition and characteristic parameters of catalyst H are shown in Table 2.
[0170] Table 1
[0171]
[0172] Note: Phosphorus content refers to the phosphorus content calculated as P2O5 based on the total mass of phosphorus-containing ZSM-5 molecular sieve.
[0173] Table 2
[0174]
[0175]
[0176] Test Example 1
[0177] The catalysts prepared in the examples and comparative examples were subjected to hydrothermal aging treatment at 820°C, 100% steam, for 20 hours, and then subjected to naphtha cracking reaction evaluation. The detailed conditions for micro-reaction evaluation are: catalyst loading 9g, feedstock oil is Yanshan Changding naphtha, the composition of which is shown in Table 3, catalyst-to-oil ratio (mass ratio of catalyst to naphtha) is 10, and reaction temperature is 600°C. The evaluation data of the reaction for 90 seconds are shown in Table 4.
[0178] Table 3
[0179]
[0180] Table 4
[0181]
[0182] It can be seen from the results in Table 4 that the application of the catalyst of the present invention in the catalytic cracking reaction of naphtha has a higher reactant conversion rate and ethylene propylene yield and a lower coke yield. At the same time, it can be shown from Table 4 that the catalyst of the present invention has good hydrothermal stability.
[0183] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalytic cracking catalyst, characterized in that: The catalyst comprises a phosphorus-containing ZSM-5 molecular sieve, a binder and clay; based on the total mass of the catalyst, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-80%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%; The proportion of the strong acid content of the catalyst to the total acid content is 50-60%; The ratio of the amount of B acid to the amount of L acid in the catalyst is 2-8.
2. The catalyst according to claim 1, wherein Based on the total mass of the catalyst, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-70%, the mass content of the clay is 5-20%, and the mass content of the binder is 16-35%; Preferably, the proportion of the strong acid content of the catalyst to the total acid content is 55-60%; Preferably, the ratio of the amount of B acid to the amount of L acid in the catalyst is 3-8; Preferably, based on the total mass of the phosphorus-containing ZSM-5 molecular sieve, the mass content of phosphorus calculated as P2O5 is 1-12%, preferably 2-9%.
3. The catalyst according to claim 1 or 2, wherein The adhesive comprises a first adhesive, a second adhesive and a third adhesive; Preferably, the first binder is obtained by calcining at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a Bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina; Preferably, the second binder is obtained by calcining aluminum sol; Preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3; Preferably, the third binder is obtained by calcining phosphate-aluminum-magnesium glue; Preferably, the mass ratio of the second binder to the first binder is 1-4, preferably 1.7-4; Preferably, the mass ratio of the second binder to the third binder is 0.1-0.9, preferably 0.2-0.
7.
4. The catalyst according to claim 3, wherein The mass ratio of Al2O3 to P2O5 in the phosphate-aluminum-magnesium glue is 0.25-0.35, and the mass of MgO is 1-5% of the sum of the mass of Al2O3 and P2O5; Preferably, the preparation method of the phosphate-aluminum-magnesium glue comprises: (a) mixing an acid-soluble aluminum precursor with water and slurrying, and then adding a phosphoric acid solution at 45-55° C. to carry out a first reaction to obtain the phosphoaluminum gel; (b) subjecting the phosphate aluminum gel obtained in step (a) to a second reaction with magnesium oxide to obtain the phosphate aluminum magnesium gel.
5. The catalyst according to claim 4, wherein The phosphoaluminum gel obtained in step (a) has a network structure; Preferably, the pH of the phosphate aluminum gel obtained in step (a) is 1-3, preferably 2-3; Preferably, the conditions of the first reaction include: temperature of 75-85°C, time of 1-2h; Preferably, the conditions of the second reaction include: temperature of 15-35°C and time of 8-12h.
6. A method for preparing a catalytic cracking catalyst, the method comprising: (1) slurrying the phosphorus-containing ZSM-5 molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry; (2) beating the first slurry with at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.2 Pa·s; (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s; (4) spray drying the third slurry and then calcining it; Wherein, the average grain size of the phosphorus-containing ZSM-5 molecular sieve is 100-500nm.
7. The method according to claim 6, wherein: The clay, phosphorus-containing ZSM-5 molecular sieve, and binder precursor are used in such amounts that, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-80%, and the mass content of the binder is 10-35%, wherein the binder is the sum of the first binder, the second binder, and the third binder; Preferably, the clay, phosphorus-containing ZSM-5 molecular sieve, and binder precursor are used in such amounts that, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the phosphorus-containing ZSM-5 molecular sieve is 60-70%, and the mass content of the binder is 16-35%, wherein the binder is the sum of the first binder, the second binder, and the third binder; Preferably, the dry basis mass ratio of the second binder precursor to the first binder precursor is 1-4, preferably 1.7-4; Preferably, the dry basis mass ratio of the second binder precursor to the third binder precursor is 0.1-0.9, preferably 0.2-0.
7.
8. The method according to claim 6, wherein: The average crystal size of the phosphorus-containing ZSM-5 molecular sieve is 200-300 nm; Preferably, the SiO2 / Al2O3 molar ratio of the phosphorus-containing ZSM-5 molecular sieve is 20-200, preferably 25-100; Preferably, based on the total mass of the phosphorus-containing ZSM-5 molecular sieve, the mass content of phosphorus calculated as P2O5 is 1-12%, preferably 2-9%.
9. The method according to any one of claims 6 to 8, wherein: The first binder precursor is selected from at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a Bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina; Preferably, the second binder precursor is aluminum sol; Preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3; Preferably, the third binder precursor is phosphate-aluminum-magnesium glue; Preferably, the mass ratio of Al2O3 to P2O5 in the phosphate-aluminum-magnesium glue is 0.25-0.35, and the mass of MgO is 1-5% of the sum of the mass of Al2O3 and P2O5.
10. The method according to claim 9, wherein: The preparation method of the phosphate-aluminum-magnesium glue comprises: (a) mixing an acid-soluble aluminum precursor with water and slurrying, and then adding a phosphoric acid solution at 45-55° C. to carry out a first reaction to obtain the phosphoaluminum gel; (b) subjecting the phosphate aluminum gel obtained in step (a) to a second reaction with magnesium oxide to obtain the phosphate aluminum magnesium gel; Preferably, the phosphoaluminum gel obtained in step (a) has a network structure; Preferably, the pH of the phosphate aluminum gel obtained in step (a) is 1-3, preferably 2-3; Preferably, the conditions of the first reaction include: temperature of 75-85°C, time of 1-2h; Preferably, the conditions of the second reaction include: temperature of 15-35°C and time of 8-12h.
11. Use of the catalytic cracking catalyst according to any one of claims 1 to 5 or the catalytic cracking catalyst obtained by the method according to any one of claims 6 to 10 in a catalytic cracking reaction, preferably in a catalytic cracking reaction of naphtha.
Citation Information
Patent Citations
Catalyst for producing propylene by catalytic cracking of naphtha, preparation method thereof, and method for producing propylene by catalytic cracking of naphtha
CN105582999B
A catalyst for naphtha catalytic cracking, its preparation method and application
CN109012742B
Method for preparing aluminum and magnesium phosphate composite bonding agents
CN102432210A
Catalytic cracking aid for increasing propylene yield, and preparation method thereof
CN107970981A
Catalytic cracking aid capable of improving octane barrels of gasoline and preparation method thereof
CN107970984A